Impresi Tindak Tutur Tidak Langsung Tidak Literal terhadap Kepekaan Sosial Peserta Didik dalam Pembelajaran di MTs Surya Buana Malang - Pripta Fajri Ramadhanti; Gigit Mujianto (Institut Agama Islam Negeri Curup, 2020)
The purposes of this study were to describe: (1) the form of indirect non-literal speech acts during learning at MTs Surya Buana Malang, (2) the function of indirect non-literal speech acts during learning at MTs Surya Buana Malang, and (3) the impressions of indirect non-literal speech acts to the social sensitivity of students at MTs Surya Buana Malang. The type of this study was qualitative with a descriptive technique. The sources of data covered the teachers and students of MTs Surya Buana Malang with the data in the form of words or utterances. The data were collected by means of recording, observing, and taking notes. Data processing techniques included: 1)making conversation transcripts and 2) describing the findings in the form of forms, functions, and impressions made by speech acts on social sensitivity during learning. Data analysis used pragmatic matching methods. The results of the study showed that there were four forms of indirect non-literal speech acts during learning with the functions of ordering, prohibiting, and requesting. Impressions or effects arising from indirect non-literal speech acts extended to being able to build students 'social sensitivity and to provide stimuli for students' social sensitivity so that they were more responsive to heed the teacher's speech